DoD depot-level reparable supply chain management : process effectiveness and opportunities for improvement - Peltz, Eric, 1968-; Brauner, Marygail K., 1947-; Keating, Edward G. (Edward Geoffrey), 1965-; Saltzman, Evan.; Tremblay, Daniel; Boren, Patricia M., 1955-; Rand eBooks (Santa Monica, CA : RAND, 2014)
The RAND National Defense Research Institute examined Department of Defense depot-level reparable (DLR) supply chain management to assess how it could be improved to enhance customer support and reduce costs. This report concludes that DLR supply chain management appears to be done relatively effectively across the services. What on the surface appears to be substantial inventory excess and high disposals of assets is instead a reflection of the fact that DLRs are durable assets very much like weapon systems and other end items. Most DLRs have very low condemnation rates, with depot maintenance economically repairing them time and again through the life of the supported end item. So when they are replaced by upgraded versions or weapon systems are phased out, demand disappears but the assets remain, leading first to (3z(Bexcess(3y (Binventory and then to disposals. This is a cost of doing business. As a result, no large, (3z(Bsilver bullet(3y (Bsolutions were found. Still, a number of modest opportunities for improving DLR supply chain management were identified. The first is improving parts supportability, including taking a total cost perspective that encompasses supply and maintenance costs when planning inventory in support of depot production. The second is to shift the Army more toward pull production. The third is to reduce lead times for all types of contracts affecting DLR supply chain management. And the fourth is to better account for all resource lead times in planning DLR production and for anticipatable shifts in procurement and repair needs. All of these enhancements would improve customer support, with better parts support likely reducing maintenance costs and pull production reducing the buildup of inventory.s
Introduction -- Findings from Item-Level Case Studies -- Parts Supportability/Taking a Total-Cost Perspective -- Adoption of Pull Production -- Reducing Contract Lead Times -- Improving Repair Planning: Anticipating Knowable Changes in Demand and Condemnations -- Potential DLR Management Changes for Exploration from the Literature -- Overall Conclusions, Recommendations, and Needs for Further Literature -- Overall Conclusions, Recommendations, and Needs for Further Research -- Appendix A: Air Force DLR Management -- Appendix B: Army DLR Management -- Appendix C: Navy DLR Management -- Appendix D: Logic to Identify DLRs -- Appendix E: Categorization of DLRs -- Appendix F: Illustrating the Consequences of a Push System.
"RAND National Defense Research Institute."
"The research was conducted by the Acquisition and Technology Policy Center of the RAND National Defense Research Institute (NDRI)"--Preface.
Includes bibliographical references (p. 141-145).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Department of Defense -- Management; United States. -- Department of Defense -- Inventory control; Business logistics -- United States -- Management; United States -- Armed Forces -- Supplies and stores -- Management; Electronic books